PEMANFAATAN LIMBAH MINYAK JELANTAH SEBAGAI BAHAN BAKU PEMBUATAN LILIN AROMATERAPI SEBAGAI INOVASI PRODUK EKOLOGIS - Nababan, Yolanda; Harefa, Meilinda Suriani; Afrianita, Yessi; Dao, Arungi Putra (Jurnal Intelek Insan Cendikia, 2025)
Environmental pollution caused by household waste disposal, particularly used cooking oil, has become a serious issue that requires sustainable solutions. This study aims to utilize waste cooking oil (commonly known as minyak jelantah) as a raw material for producing aromatherapy candles that are both useful and environmentally friendly. The research employed a descriptive-experimental method, beginning with the collection and purification of the used oil using activated charcoal, followed by mixing it with additives such as stearic acid, coloring agents, and essential oils. The findings revealed that the purified oil produced candles with bright colors, pleasant fragrances, solid textures, and stable burning performance without excessive smoke. This innovation not only helps reduce water and soil pollution but also creates new economic opportunities through eco-friendly products with high market value. The utilization of used cooking oil for aromatherapy candle production reflects the application of circular economy principles and serves as a practical step toward fostering public awareness of sustainable waste management.